Kebhinekaan dan Keberagaman : Kerukunan Umat Beragama di Tengah Pluralitas - Sari, Melta (Lembaga Yasin AlSys, 2022)
Indonesia is a country that has a fairly high level of plurality, both in the fields of language, ethnicity, and religion. The plurality of religion and belief in Indonesia requires an equal, non-discriminatory and non-violent space for religious expression. Therefore, the state through its constitution guarantees every citizen to embrace religion and worship according to his religion and belief. Religion should be a medium that makes people live in harmony and peace, without being hostile to each other, dividing, let alone causing casualties. Various solutions have been sought and have even been implemented, including dialogue to find common ground between religions and drafting inter-religious cooperation plans in order to build the nation. It is necessary to build awareness of the importance of understanding that the reality of religious diversity in social life is a sunnatullah that cannot be avoided, such awareness must be built in families, educational institutions and other social institutions.